Goodbye, Eating Disorders. Issue 5 (20th October 2017) - Cohn, Leigh
ABSTRACT: In 1977, I fell in love at first sight, and since then eating disorders have been a central part of my life. As I step down after 25 years as editor of Eating Disorders: The Journal of Treatment and Prevention, I am also saying goodbye to the eating disorders field and moving on to retirement and other areas of interest. In this Last Word article, I will write about my history with the journal and the field and use this forum to thank a few of the people I've known along the way.